Occurrences of aquatic mammals in the State of Pernambuco, Brazil: Marine Mammals, Pernambuco, Brazil - Loffler Niemeyer Attademo, Fernanda; Xavier do Nascimento, João Luiz; Pereira de Sousa, Glaucia; Gomes Borges, João Carlos; Einhardt Vergara Parente, Jociery; Barboza de Alencar, Ana Emília; Frederico da Costa Foppel, Ernesto; Carlos da Boaviagem Freire, Augusto; Pinto de Lima, Régis; de Oliveira Luna, Fábia; Elvis Matias de Oliveira, Radan (Arquivos de Ciências do Mar, 2020)
Aquatic mammals occur throughout the Brazil territory. However, until now there are no descriptions of the species that occur in the coast of Pernambuco State. Stranding assistance is an important tool for the record of aquatic mammal species and for obtaining information about populations and their respective threats. This study aimed to describe the occurrence, diversity and distribution of aquatic mammals in Pernambuco State, Brazil. The knowledge acquired came from the database from institutions within the Northeast Marine Mammals Stranding Network (REMANE) that acted in the state between 1984 and 2015, contemplating live and dead animals. A number of 157 stranding events were recorded in Pernambuco State, corresponding to 18 aquatic mammal species. Sotalia guianensis was the most abundant species (28,7%), followed by Tursiops truncatus (17,2%) and Trichechus manatus (9,6%). The presence of threatened and migratory species was identified, being the anthropic activities the biggest threat. Recife counties and the Olinda County presented itself as discontinued area of the marine manatee; however, this study showed the occurrence of native animals in these localities. Systematized assistance to stranding and educational campaigns are essentials to guarantee the conservations of these species in Pernambuco.